Penerapan Metode Multifactor Evaluation Process (MFEP) Untuk Menentukan Kelayakan Penerima Bantuan Pinjaman Modal Usaha Kecil Menengah - Ramadhani, Winda Ayu; Irawati, Novica; Maulana, Cecep (Forum Kerjasama Pendidikan Tinggi, 2022)
During the Covid-19 pandemic, the government made a revolving business capital assistance program, which is one of the program plans from the Durian Village Owned Enterprise (BUMDes) in Sei Balai District which was created to address economic problems within the Durian Village, Sei Balai District. This revolving business capital assistance program in the form of credit funds was created to improve the quality of life of the poor by disbursing capital credit assistance to assist rural communities in developing businesses that were previously affected by the Covid-19 pandemic, making small businesses such as brick makers, pots, ornamental plants and farmers experience difficulties. the decrease in income in the village, then from the revolving business capital assistance program the targets of this program are small and medium enterprises (SMEs). So far, prospective recipients of funds at BUMDes Durian are still determined by holding a meeting by the Village Head and data storage and data processing of prospective recipients are still using Microsoft Office Word, which of course makes BUMDes take relatively longer time to make decisions. This old system is less effective because it cannot determine potential recipients of funds in a short time. For this reason, it is necessary to establish a new system that can be used to determine potential recipients of funds more easily and assist BUMDes in determining the eligibility of prospective beneficiaries of targeted assistance. The MFEP method is a multi-criteria decision support technique, that each alternative used consists of a number of criteria with values and each criterion itself has a weight to describe how important these criteria are compared to other criteria.